2023
DOI: 10.1002/ijgo.14947
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic options for the management of abnormal uterine bleeding

Abstract: Just as the investigation of abnormal uterine bleeding (AUB) is approached systematically using the two FIGO systems for AUB in the reproductive years, treatment options can be considered similarly. Therapeutic options fall into two categories—medical and surgical—and while medical management is typically regarded as first‐line therapy, there are several exceptions defined by the presenting cause or causes, mainly when infertility is a concurrent issue. In the early 1990s, up to 60% of women underwent a hyster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 130 publications
0
2
0
Order By: Relevance
“…Surgical modalities for AUB management include endometrial ablation, hysterectomy, dilation and curettage (D&C), hysteroscopy with D&C, polypectomy, myomectomy and uterine artery embolization. 92 Endometrial ablation may be considered for patients without uterine abnormality who desire reduced menstrual blood loss and dysmenorrhea. It involves the use of an energy source to destroy the endometrial lining, and should therefore be avoided in women of childbearing age.…”
Section: Reviewmentioning
confidence: 99%
“…Surgical modalities for AUB management include endometrial ablation, hysterectomy, dilation and curettage (D&C), hysteroscopy with D&C, polypectomy, myomectomy and uterine artery embolization. 92 Endometrial ablation may be considered for patients without uterine abnormality who desire reduced menstrual blood loss and dysmenorrhea. It involves the use of an energy source to destroy the endometrial lining, and should therefore be avoided in women of childbearing age.…”
Section: Reviewmentioning
confidence: 99%
“… 40 , 41 , 42 , 43 , 44 This risk is exemplified by evaluating iron‐dependent erythropoiesis in women with and without HMB, 2 and a Finnish study of women with HMB showed that 27% of its participants had IDA, 90% with a serum ferritin less than 30 µg/L, and 60% with serum ferritin levels below 15 µg/L. 45 Effective diagnostic and therapeutic strategies exist for the varying causes of the symptoms of HMB 46 , 47 ; failure to identify and address this issue will prolong or even prevent the sustained normalization of iron stores. Moreover, it is of importance to screen females experiencing HMB and recurrent or refractory IDA without uterine organic lesions for congenital bleeding disorders (CBDs) such as platelet function disorders and von Willebrand disease (VWD).…”
Section: Diagnosismentioning
confidence: 99%